Motivasi Indonesia menandatangani Preferential Trade Agreement (PTA) dengan Pakistan Tahun 2012 - Hafiz, Khairul; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study analyzes the factors that motivate Indonesia signed apreferential trade agreement with Pakistan in 2012 . the reasons which promptedIndonesia to cooperate with Pakistan to better cooperation , free tradeagreements . This study will also explain the Indonesian trip begins negotiationsof the Framework on Comprehensive Economic Partnership ( FACEP ) byIndonesia and Pakistan signed in 2005 , both from the development and scope ofnegotiations .Keywords: Preferential Trade Agreement, Cooperation, Factors.